Evaluation of Vehicle Tyre Aging Awareness as a Potential Hazard to Road Users in Ghana - Arnold DUMENYA; Maxwell Selase AKPLE; Emmanuel Obobi TETTEHFIO (International Journal of Engineering and Management Research, 2022)
This study aimed to investigate tyre aging awareness level among various tyre users and determine their abilities to decode the date of manufacture (DOM) from Department of Transport (DOT) tyre identification number (TIN) printed on tyre’s sidewall. The study was carried out within the Accra Metropolitan and Ho Municipal Assemblies in Ghana. Data was obtained through the administration of 1191 questionnaires using simple random sampling technique to tyre consumers consisting of drivers (1021), vulcanizers (120) and tyre dealers (50). Analyses of the results showed that majority of participants (77.5%) were aware of aging occurring in vehicle tyres but only 7.5% identified it as potential hazard to road users. The results also showed that participants had difficulty in decoding and interpreting information from the DOT’s TIN. Majority of the participants (over 60%) were able to interpret the numeric denoting rim sizes correctly yet only 16.8% construed “R” as radial ply type of tyre construction. Furthermore, most participants were not able to determine the DOM accurately in the week/year format from other tyre markings. There was negative correlation between gender and educational levels of participants and their ability to decode DOM in the various formats from other tyre markings. The implication from the study suggest that most Ghanaian tyre consumers cannot decode very vital tyre information from DOT’s TIN, thus training and education is recommended for various stakeholders in the tyre industry.